Can Green Finance Policies Slow Greenhouse Gas Emissions? Evidence from China’s Manufacturing Sector - Shen , Zhao; Yuxuan, Song (Journal of Ecohumanism, 2024)
Reducing greenhouse gas emissions is not only an inevitable requirement for the construction of ecological civilization, but also a key step to enhance high-quality development. Based on the current research situation, this paper uses the DID (Difference- Difference) method to test and explore the influence mechanism of Green Finance Reform and Innovation Pilot zone (GFRI) policy on greenhouse gas emissions (GHG) of Chinese manufacturing enterprises in a multi-dimensional way, and further analyzes the industry and spatial variability of the influence of green finance policy, and puts forward corresponding policy recommendations based on the empirical results.